2003
DOI: 10.1590/s1516-635x2003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Performance and organ morphology of broilers fed microbial or antimicrobial additives and raised in batteries or floor pens

Abstract: This study was conducted to determine the effect of microbial or antimicrobial additives on the performance and organ morphology of broilers raised in batteries or in floor pens. The effect of microbial additives on the presence of oocysts in the litter was also studied. Experiments 1 and 2 consisted of four treatments (non-supplemented control diet or diet supplemented with avilamycin, bacitracin methylene disalicylate or enramycin) and six repetitions in a randomized block design. In Experiment 1, 288 day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…The dietary supplementation of broilers with B. subtilis as probiotic significantly increased the relative weight of spleen by 3.8% without significantly affecting the relative weights of liver and bursa of Fabricius 43 . In agreement with our study, Pedroso et al reported that the dietary inclusion of Lactobacillus reuteri and L. johnsonii as probiotics significantly increased intestinal weight in 21-day old broilers 44 . Probiotics effect on the weight of visceral organs and intestines of animals is inexplicit, and can also be determined by the nature and amount of microbial strains used as probiotics.…”
Section: Discussionsupporting
confidence: 93%
“…The dietary supplementation of broilers with B. subtilis as probiotic significantly increased the relative weight of spleen by 3.8% without significantly affecting the relative weights of liver and bursa of Fabricius 43 . In agreement with our study, Pedroso et al reported that the dietary inclusion of Lactobacillus reuteri and L. johnsonii as probiotics significantly increased intestinal weight in 21-day old broilers 44 . Probiotics effect on the weight of visceral organs and intestines of animals is inexplicit, and can also be determined by the nature and amount of microbial strains used as probiotics.…”
Section: Discussionsupporting
confidence: 93%
“…Such findings have been reported in the literature. For example, Pedroso et al (2003) added Lactobacillus reuteri and L. johnsonii into drinking water and reported a significant increase in intestinal weight in 21-day-old broilers. The mechanism by which this occurs is not known as the effect of probiotics on organ weights in animals is equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tested more than one type of probiotic, so that some treatments did not meet the inclusion criteria: only spray administration of probiotic (Leandro et al, 2001), and probiotic administered only via drinking water (Pedroso et al, 2003;Pelicano et al, 2004 b;Teixeira et al, 2003).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…A) Lactobacillus reuteri and Lactobacillus jonhsonii in the drinking water at one day of age + Bacillus subtilis in the diet (Loddi, 2003;Pedroso et al, 2003;Sato, 2001 and Saccharomyces cerevisiae in the diet (Cavalcanti, 1995;Henrique, 1998;Teixeira et al, 2003). G) Bacillus toyoi in the diet (Zuanon et al, 1998a,b Hedges, 1982.…”
Section: Systematic Reviewmentioning
confidence: 99%